1996
DOI: 10.1557/proc-449-1085
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Defects on the Characteristics of GaN Schottky Diodes

Abstract: We have studied the fabrication of Pt/Au Schottky diodes on n-type GaN. We show that the electrical characteristics of the diodes are strongly dependent on the surface chemical treatment before the metal deposition. Lowest leakage currents were obtained by the use of a HC1 solution. We also show that annealing the diode at a moderate temperature (400°C) leads to reduced reverse currents. In order to explain these results, we measured the density of deep levels in the Schottky diode depletion region before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…These results indicate that the electrical properties of the Ru/Ti/n-InP SBD strongly influenced by the annealing temperature. According to Duboz et al [14], the lower value of the barrier height for the sample annealed at higher temperature can be attributed to reduction in the density of interfacial defects. The modification of the defect density by annealing could change the pinning at the Fermi level resulted in a change of the barrier heights.…”
Section: Resultsmentioning
confidence: 93%
“…These results indicate that the electrical properties of the Ru/Ti/n-InP SBD strongly influenced by the annealing temperature. According to Duboz et al [14], the lower value of the barrier height for the sample annealed at higher temperature can be attributed to reduction in the density of interfacial defects. The modification of the defect density by annealing could change the pinning at the Fermi level resulted in a change of the barrier heights.…”
Section: Resultsmentioning
confidence: 93%
“…Detailed Schottky diode studies were reported for various metal contacts on n-GaN [7][8][9][10][11][12]. Recently, the dependence of device parameters on threading dislocations in GaN based light emitting diodes (LEDs) and Schottky diodes fabricated on different substrates or templates were reported [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This improvement can be attributed to the reduction of density of interfacial defects. 18 However, as the annealing temperatures increased further, the I -V characteristics of SCs deteriorated in both cases. The degradation is attributed to the creation of shunt paths 11 due to the deep diffusion of Ni atoms into GaN layer, as illustrated in Fig.…”
mentioning
confidence: 95%